Management of Pediatric Kidney Transplant Patients During the COVID-19 Pandemic: Guidance From the Canadian Society of Transplantation Pediatric Group. (November 2020) - Teoh, Chia Wei; Gaudreault-Tremblay, Marie-Michele; Blydt-Hansen, Tom D.; Goldberg, Aviva; Arora, Steven; Feber, Janusz; Langlois, Valerie; Ruhl, Michelle; Phan, Veronique; Morgan, Catherine; Acott, Philip; Hamiwka, Lorraine
Purpose of the program: To provide guidance on the management of pediatric kidney transplant patients during the COVID-19 pandemic. Sources of information: Program-specific documents, preexisting, and related to COVID-19; documents from provincial, national, and international kidney transplant societies/agencies and organ procurement agencies; national and international webinars, including webinars that we hosted for input and feedback; with additional information from formal and informal review of published academic literature. Methods: Challenges in the care of pediatric kidney transplant patients during the COVID-19 pandemic were highlighted within the Canadian Society of Transplantation (CST) Pediatric Group. It identified pediatric kidney transplant nephrologists (including a pediatric nephrologist ethicist) across the country and formed a workgroup. The initial guidance document was drafted and members of the workgroup reviewed and discussed all suggestions in detail via e-mail and virtual meetings. Disagreements were resolved by consensus. The document was reviewed by the CST Kidney Transplant Working Group, by the Canadian Society of Nephrology (CSN) COVID-19 Rapid Response Team (RRT), and an infectious disease expert. The suggestions were presented at an interactive webinar sponsored by CSN in collaboration with the CST and Canadian Association of Pediatric Nephrologists (CAPN), and attended by pediatric kidney health care professionals for further peer input. Final revisions were made based on feedback received. CJKHD editors reviewed the parallel process peer review and edited the manuscript for clarity. Key findings: We identified 8 key areas of pediatric kidney transplant care that may be affected by the COVID-19 pandemic: (1) transplant activity, (2) outpatient clinic activity, (3) monitoring, (4) multidisciplinary care, (5) medications (immunosuppression and others), (6) patient/family education/support, (7) school and employment, and (8) management of pediatric kidney transplant patients who are COVID-19 positive. We make specific suggestions for each of these areas. Limitations: A full systematic review of available literature was not undertaken for the sake of expediency in development of this guideline. There is a paucity of literature to support evidence-based recommendations at this time. Instead, these guidelines were formulated based on expert opinion derived from available knowledge/experience and are subject to the biases associated with this level of evidence. The parallel review process that was created to expedite the publication of this work may not be as robust as standard arms' length peer review processes. Implications: These recommendations are meant to serve as a guide to pediatric kidney transplant directors, clinicians, and administrators for providing the best patient care in the context of limited resources while protecting patients and health care providers wherever possible by limiting exposure to COVID-19. We recognize that recommendations may not be applicable to all provincial/local health authority practices and that they may not be delivered to all patients given the time and resource constraints affecting the individual provincial/local health jurisdiction.